The Role of Fee-Based Income on the Financial Performance of Conventional Commercial Banks in Indonesia - Abimanyu; Rinaldi Rustam; Mona Adriana Sutrisno (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the role of Fee-Based Income on the financial performance of conventional commercial banks in Indonesia during the period 2018–2023. The primary focus of this research is to explore the contribution of Fee-Based Income to the total bank revenue, identify the factors driving the increase in non-interest income, and analyze its impact on financial performance indicators, particularly Return on Assets (ROA). The data used in this study is secondary data obtained from the annual reports of conventional commercial banks listed on the Indonesia Stock Exchange (IDX) for the 2018–2023 period. The variables analyzed include Fee-Based Income, Interest Rate, Inflation, Exchange Rate, as well as several financial ratios such as BOPO (Operating Expenses to Operating Income), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), and Return on Assets (ROA). Using a quantitative approach with statistical analysis methods, this study finds that Fee-Based Income shows a rising trend in its contribution to total bank revenue, driven by digital efficiency and product diversification strategies. The analysis also indicates that an increase in Fee-Based Income has a significant impact on bank profitability, as reflected in the ROA ratio. These findings offer both theoretical and practical contributions to understanding the shifting structure of banking income and strategies for improving the financial performance of conventional commercial banks in the digital era.